1983
DOI: 10.1111/j.1365-2265.1983.tb00738.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Osteodystrophy in Primary Biliary Cirrhosis: A Possible Defect in Kupffer Cell Mediated Cleavage of Parathyroid Hormone

Abstract: Twelve of fourteen female patients with primary biliary cirrhosis, receiving vitamin D supplementation, exhibited unequivocal signs of osteoporosis but not of osteomalacia. Vitamin D treatment reproduced normal 25-hydroxyvitamin D levels in all but two patients and the 1,25 and 24,25-dihydroxyvitamin D metabolic pathways appeared to be unimpaired. A possible mechanism for the vitamin D resistant osteoporosis has been identified following the observation that, in those patients with severe cirrhosis, the circul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1

Year Published

1984
1984
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…Another report showed that the increase in bone resorption might be the result of decreased PTH degradation [41]. In our study, while serum PTH and CTX levels were higher in children with chronic hepatitis B than in healthy controls, there was no significant different in respect to serum osteocalcin and ALP levels.…”
Section: Discussioncontrasting
confidence: 54%
“…Another report showed that the increase in bone resorption might be the result of decreased PTH degradation [41]. In our study, while serum PTH and CTX levels were higher in children with chronic hepatitis B than in healthy controls, there was no significant different in respect to serum osteocalcin and ALP levels.…”
Section: Discussioncontrasting
confidence: 54%
“…They've hypothesized that the elevation of intact PTH in patients with primary biliary cirrhosis is due to defective Kupffer cell-mediated cleavage of the hormone. [16] The study conducted by Kirch et al in 1990 revealed that although the level of albumin-corrected total calcium levels of patients with liver cirrhosis were on the lower limit of normal, the corrected calcium and PTH were positively correlated, which signifies that the elevated levels of PTH is not reactive to calcium depletion. They've concluded that the midregion PTH fragments are increased in patients with liver cirrhosis rather than the intact hormone.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicate that patients with PBC have primarily osteomalacia [157,158], others find mostly osteoporosis [159][160][161][162], others find a high prevalence of both osteomalacia and osteoporosis [163,164], and still others find little of either [165][166][167][168]. PBC is a disease primarily of middle-aged women, an age at which postmenopausal osteoporosis is common and not readily distinguished from the osteoporosis of the liver disease.…”
Section: Incidence and Prevalencementioning
confidence: 99%